Heavy Alcohol Use Is Associated With Gastric Cancer: Analysis of the National Health and Nutrition Examination Survey From 1999 to 2010. (9th May 2021) - Laszkowska, Monika; Rodriguez, Steven; Kim, Judith; Hur, Chin
Abstract : INTRODUCTION: Evidence regarding the association between alcohol use and gastric cancer (GC) has been inconsistent. METHODS: Adults who participated in the National Health and Nutrition Examination Survey (NHANES) from 1999 to 2010 were included. Multivariable regression was used to assess the association between GC and heavy alcohol use (≥5 alcoholic drinks daily). RESULTS: Of 470, 168 individuals surveyed, 342 had a history of GC. Heavy alcohol use was associated with GC (odds ratio 3.13, 95% confidence interval 1.15–8.64) on multivariable analysis. DISCUSSION: This is the largest study to our knowledge to demonstrate an association between heavy alcohol use and GC in the United States.